Teaching mathematics at the college - Zenkevičienė, Marytė; Grigalevičienė, Emilė (Lietuvos matematikos rinkinys, 2005)
In the report the meaning of the mathematics subject is analyzed, achieving the goals of the non-university studies' programs. The report shares the experience how the goals of mathematics' subject is achieved, how the personal students' work is organized in Alytus and Marijampole colleges. The system of the accumulated assessment and its advantages are reviewed in this report.
Keywords: account tally; development of skills; intermediate reckons; final assessment; methods of mathematical modeling; practical works; purpose of mathematics; self-sufficient work